SUBSYTEM OF EXERCISES FOR THE FORMATION OF FUTURE TEACHERS' LEXICAL COMPETENCE IN TEACHING ENGLISH AFTER GERMAN - Наталія Жовтюк (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The necessity of taking into consideration features of the first foreign language lexical system and its possible impact on the process of second language acquisition for forming future teachers' lexical competence in teaching English after German has been grounded in the article. Stages of lexical competence acquisition in teaching English after German have been defined and characterized and a subsystem of exercises for forming future teachers' lexical competence in teaching English after German has been presented. The subsystem includes a group of exercises for familiarization and semantization of new lexical units; a group of exercises to automatize students' actions with new lexical units at the level of word forms, expression, phrase/sentence, complex syntactic unit; a group of exercises to improve students lexical skills in communicative situations. Examples of each group of exercises have been presented in the article.